Distribution of Geological Structures on Java Island Based on Derivative Analysis of Satellite Gravity Data - Permana, Nanda Ridki; Fadrian, Dhika Faiz; Gunawan, Belista; Wulandari, Amara (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2024)
The island of Java is an interesting place to study geology because of the various tectonic processes that occur starting from volcanic activity, changes in relief, and the relative movement of faults. The aim of this research is to determine the distribution of geological structures spread throughout Java Island based on fault analysis from gravity satellite data. Gravity data was taken via the ICGEM website with a data resolution of 2 km so that 10,000 data were obtained consisting of gravitational disturbances (GD), geoid, and Digital Elevation Model (DEM). The data processing results represent weak zones on the residual anomaly map where fault movement occurs with low anomaly values, namely -55,147 – (-27,175) mGal which stretches from West Java to southern Madura. On the FHD map, it can be seen that the distribution of maximum gravity anomalies is quite numerous and complex with an anomaly value of 1117.18 mGal. It is suspected that the fault near the mountain occurred due to volcanic processes and the southern part occurred due to the shifting process of the Indo-Australian plate and the Eurasian plate. On the TDR map, the weak zones caused by faults spread across Java Island have low gravity anomaly values ranging from -1,353 – (-0.833) mGal. In the Banten to West Java area there are the Baribis Fault and the Cimandiri Fault. In the Central Java region there are the Ajibarang, Ungaran, Baribis Kendeng and Pati faults, as well as parts of the Special Region of Yogyakarta there is the Opak fault. Meanwhile, in the East Java area there are the Baribis Kendeng, Pasuran and Probolinggo faults.